2010
DOI: 10.1016/j.otsr.2010.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The lumbar-pelvic-femoral complex: applications in spinal imbalance

Abstract: The pelvis may be seen as a single vertebra, between the spine and the femurs. The anatomy of this pelvic vertebra has changed with the evolution of species, notably with the transition to bipedalism, with the consequent appearance of lumbar lordosis. The lumbosacral angle, almost non-existent in other mammals, is at its greatest in humans. Pelvic and spinal radiological parameters reflect the sagittal balance of the spine in bipedal humanity. Applications in the management of spinal imbalance are numerous. Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…The left‐bias in the false pelvis uncovered in this study may correspond with the biomechanical requirements of the lumbar‐pelvic‐femoral complex that transmits the weight of the trunk to the lower limbs during locomotion (Husson et al, ; Lazennec et al, ; Tardieu et al, ). Previous studies report a systematic left‐bias in the sacrum (Plochocki, ; Tague, ), which is corroborated by this study's finding that SAS1L (the auricular surface length of the first sacral vertebra) exhibited the greatest left‐bias of any pelvic measure (mean DA = −4.45), and the only variable to exhibit significant bilateral asymmetry in both males and females.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The left‐bias in the false pelvis uncovered in this study may correspond with the biomechanical requirements of the lumbar‐pelvic‐femoral complex that transmits the weight of the trunk to the lower limbs during locomotion (Husson et al, ; Lazennec et al, ; Tardieu et al, ). Previous studies report a systematic left‐bias in the sacrum (Plochocki, ; Tague, ), which is corroborated by this study's finding that SAS1L (the auricular surface length of the first sacral vertebra) exhibited the greatest left‐bias of any pelvic measure (mean DA = −4.45), and the only variable to exhibit significant bilateral asymmetry in both males and females.…”
Section: Discussionmentioning
confidence: 55%
“…The sacrum serves as the pivot point for the upper body, and has been suggested to dynamically respond to the right‐bias of the upper limbs with a left‐directional bias (Plochocki, ; Tague, ). Following the biomechanical requirements of the pelvis in supporting the trunk in the orthograde posture necessitated by bipedal locomotion (Husson et al, ; Lazennec et al, ), the left‐bias in the posterior pelvic canal may be similarly related to biomechanical function. This hypothesis gains credence in considering that the midplane and outlet posterior measures are both taken from the S4‐S5 fusion line.…”
Section: Discussionmentioning
confidence: 99%
“…4 compares three participants, one with T4/T12 kyphosis and L1/L5 lordosis angles close to the average values of the participants sample (mean7SD T4/T12 angle: 33.9°711.0; L1/L5 angle: 39.7°78.2) (4a), one with high T4-T12 kyphosis angle (4b) and one with high L1-L5 lordosis angle (4c). It was showed that kyphosis and lordosis angles were highly dependent on the pelvic incidence in the mechanism of maintenance of sagittal alignment (Legaye et al, 1998;Vaz et al, 2002;Skalli et al, 2007;Husson et al, 2010;Lazennec et al, 2013;Vialle et al, 2005). Pelvic incidence is a parameter defined as the angle between the perpendicular to the sacral plate at its midpoint and the line connecting this point to the femoral heads axis (Schwab et al, 2006).…”
Section: Tablementioning
confidence: 99%
“…The pelvis has been described as an intercalary bone in the lumbar-pelvic-femoral complex, or a ''pelvic vertebra'' [17,22], such that pelvic tilt is dependent on spinal and femoral alignment. As a patient sits with 90°of apparent hip flexion (brings his or her femurs approximately 90°to the vertical plane), there will be motion through the lumbar spine segments and/or the femoroacetabular articulation in the lumbar-pelvic-femoral complex.…”
Section: Introductionmentioning
confidence: 99%